Predictors of IAPT psychological well-being practitioners' intention to use CBT self-help materials routinely in their clinical practice. (1st June 2016) - Levy, Michelle A.; Holttum, Sue; Dooley, Jemima; Ononaiye, Margo
Abstract: Despite efficacy and effectiveness evidence, and recommendations from the National Institute for Health and Care Excellence (NICE), use of CBT self-help materials remains inconsistent in UK mental health services. Since 2006, the Improving Access to Psychological Therapies (IAPT) programme has provided standardized training and mandates routine use of CBT self-help materials by their trainee psychological well-being practitioners (PWPs). This study tested whether the main constructs of the theory of planned behaviour (TPB; attitudes, subjective norms, and perceived behavioural control), past use, prior training and demographic characteristics, would predict PWPs' intention to use self-help materials routinely in their clinical practice. Stage 1 utilized a standardized procedure to create measures for the constructs of TPB, before the design and testing of a web-based, cross-sectional questionnaire. In stage 2, the questionnaire was administered to a convenience sample of trainee PWPs ( n = 94). Data was analysed using multiple linear regression, mediation analyses, and content analysis. TPB constructs predicted intention to use self-help materials, with only direct attitude contributing significantly to 70% of the variance in intention. Past use of materials predicted intention, via direct and indirect mediation. Qualitative data from 43 trainees highlighted clients' experience of self-help materials as positive, albeit with some practical constraints. The results suggest that the main constructs of TPB have some utility in predicting trainee PWPs' intention to use self-help materials routinely. Future prospective, longitudinal research could investigate actual use of self-help materials to elucidate cognitive factors involved in trainees' clinical decision-making post-qualification.